ENVIRONMENTAL, SOCIAL, AND GOVERNANCE PILLARS AND TAX AVOIDANCE: A FUTURE RESEARCH AGENDA IN INDONESIA - Andrianto, Alfian; Sudaryono, Eko Arief; Aryani, Y Anni; Setiawan, Doddy (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Taxes are Indonesia's main source of state revenue, yet tax avoidance remains a persistent challenge. At the same time, Environmental, Social, and Governance (ESG) practices are increasingly recognized as mechanisms to improve corporate transparency and accountability. However, the relationship between ESG pillars and tax avoidance in Indonesia has not been systematically reviewed. This study aims to map prior evidence and propose a future research agenda. A Systematic Literature Review (SLR) of 66 articles published in Sinta-1 and Sinta-2 accredited journals during 2015–2025 was conducted using the PICO framework and a charting the field approach. The findings show that the Governance pillar dominates (87.6% of proxies), with institutional ownership, audit committees, and independent commissioners as the most common variables. The Social and Environmental pillars remain underexplored, while the Effective Tax Rate (ETR) is the most widely used tax avoidance measure. This study recommends diversifying ESG indicators, broadening tax avoidance measures, and employing varied methodologies. Its contribution lies in providing a comprehensive mapping and a concrete agenda to close conceptual and methodological gaps.